High Cholesterol Diet-Induced Changes in Oxysterol and Scavenger Receptor Levels in Heart Tissue - SÖZEN, AHMET ERDİ; ŞAHİN, ALİ; KARTAL ÖZER, NESRİN (HINDAWI LTD, 2018)
Involvement of high cholesterol and oxidative stress in cardiovascular diseases is well studied, as it can be hypothesized that various products originated from lipid peroxidation, such as oxysterols, or affected protein expression might lead to cardiomyocyte damage followed by the pathological modifications. Although oxidation of excessive cholesterol to oxysterols in elevated stress conditions is identified by a number of studies, the role of a high cholesterol diet in regulating fatty acid and oxysterol accumulation, together with scavenger receptor mRNA levels, in the heart remains little investigated. Our study provides a detailed analysis of the changes in fatty acid, oxysterol, and scavenger receptor profiles and its relation with histological alterations in the heart tissue. We evaluated alterations of fatty acid composition, by the GC-MS method, while 4 beta-, 25-, and 27-hydroxycholesterol and 7-ketocholesterol levels by means of LC-MS/MS in high cholesterol diet-fed rabbits. Additionally, a number of proteins related to lipid metabolism and scavenger receptor mRNA expressions were evaluated by Western blotting and RT-PCR. According to our in vivo results, a high cholesterol diet enhances a number of unsaturated fatty acids, oxysterols, and LXR alpha, in addition to CD36, CD68, CD204, and SR-FI expressions while alpha-tocopherol supplementation decreases LXR alpha and SR expressions together with an increase in 27-hydroxycholesterol and ABCA1 levels. Our results indicated that the high cholesterol diet modulates proteins related to lipid metabolism, which might result in the malfunction of the heart and alpha-tocopherol shows its beneficial effects. We believe that this work will lead the generation of different theories in the development of heart diseases.
Keywords: HYPERCHOLESTEROLEMIA-INDUCED ATHEROSCLEROSIS; ALPHA-TOCOPHEROL; OXIDATIVE STRESS; VITAMIN-E; DENSITY-LIPOPROTEIN; ENDOTHELIAL-CELLS; FATTY-ACIDS; LXR-ALPHA; METABOLISM; DISEASE